Progressive training model for muscle hypertrophy and strength gain - Ozaki, H.; Abe, T.; Machida, S.; Naito, H. (Advances in Exercise and Sports Physiology, 2017)
Based on the findings of previous research, in the present study, we aimed to establish a progressive training model for older adults as well as young and middle-aged adults, including subjects undergoing rehabilitation and trained subjects, for maintaining or increasing muscle mass and strength by discussing the potential interaction among the following three factors: exercise load, muscular fatigue, and speed of movement. All these factors usually enhance muscle growth by maximizing muscle fiber recruitment and fast-twitch fiber utilization. Neuromuscular electrical stimulation and endurance exercise, such as walking and cycling, can induce muscle hypertrophy and strength gain to different extents for certain muscles (working muscles) and/or age groups. Moreover, the development of muscular fatigue via blood flow restriction in working muscles can enhance the hypertrophic effect. Ensuring greater speed while walking also appears to yield greater strength gain in older adults. However, the addition of resistance exercise to the exercise program of individuals who regularly perform endurance exercise may be effective for maintaining or increasing muscle mass and strength. As the effects of body mass-based resistance training (RT) depend on the relative value of muscle strength to body mass and the muscle size before intervention, RT with external weights would need to be employed for trained subjects. Recent research has demonstrated that low external weight training can induce hypertrophy that is comparable to that induced by high external weight training when each set is performed until lifting failure. Nevertheless, favorable strength gain is achieved when high external load is used. Furthermore, previous studies indicated that higher lifting speed during RT can result in greater strength gain in young adults, although this finding is not always observed in older adults. Hence, it is important to understand the characteristics of each training method to assign the most suitable training program based on the individual's fitness level and goals.